Studying the Microanatomy of the Heart in Three Dimensions: A Practical Update - Jarvis, Jonathan C.; Stephenson, Robert S. (Frontiers in Pediatrics, 2013)
The structure and function of the heart needs to be understood in 3 dimensions. We give a brief historical summary of the methods by which such an understanding has been sought, and some practical details of the relatively new technique of micro CT with iodine contrast enhancement in samples from rat and rabbit. We discuss how the improved anatomical detail available in fixed cadaveric hearts will enhance our ability to model and to understand the integrated function of the cardiomyocytes, conducting tissues and fibrous supporting structures that generate the pumping function of the heart.